Ilustracje z dziewiętnastowiecznej prasy Królestwa Polskiego jako źródło do badań nad kulturą uzdrowiskową - Kita, Jarosław (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2015)
In the second half of the XIXth century in Polish Kingdom there has been substantial progress in the development of printing techniques. This observations also applies to illustrative graphics. Woodcut as a technique of describing the event, designed to press pictures was cultivated by the most outstanding artists. Thanks it, illustrated magazines in Polish Kingdom developed quickly and belonged to the most widely read publications. In the papers of this magazines appeared number iconographic motif, such as: views of various buildings and equipment, panoramas and landscapes commanded places and cities, portrait of eminent and merit person. At that time took place a revitalization of health resort culture in medical fields. As it were, the qualities of long known European resorts were being “discovered” anew and the native health resorts and spas were becoming more and more popular. Not only was the medical treatment the purpose to visit the spa but it become a fashion and important in term of social contacts. So let’s pose the question if the wide concept of health resort culture also found in rang of interests of creators illustrative graphics then? Is among the various iconographic motifs appeared woodcut showing the facilities and equipment located in the areas of spas? If so, were only illustrated object designed for balneotherapy and hydrotherapy, or also appeared object designed for entertainment and making free time more pleasant. Moreover, were published portraits of merit for the development of the resort culture on the columns of the Polish Kingdom press? The basis for this analysis were the illustrated magazines appearing on the terrain of Polish Kingdom in XIXth and early XXth century. These periodicals were reaching mainly these social groups from which the patients of health resorts derived, and these magazines were widely read throughout all the land then Polish.